Survey study of effective factors on maternal mortality in Kurdestan province from 1998 to 2002 - Golyan Tehrani Sh; Holakoei K; Zarei M (Tehran University of Medical Sciences, 2004)
Introduction: Pregnancy is a natural phenomena and basis of birth but can induce various dangers to mother and fetus. Since mother is the central part of family, maternal mortality would be an irreparable damage to the community. On average 10100 live births and 12 maternal mortalities occur in Kurdestan province each year; the maternal mortality rate is therefore 118/100000 live births which in comparison to similar figure in whole country (37/100000 live births) is three times higher. Materials and Methods: This research is an analytic case-control study. Cases and controls were matched for place of residence and age at gestation. Cases (n=55) were chosen by census and controls (n=220) were chosen by random sampling. The tool used to collect data was questionnaire, validity and reliability of which was tested by content validity and test-retest method. The statistical testing used in this study were Chi square and odds ratio. Data were analyzed by SPSS .11 software. Results: Most of maternal mortalities had occurred in women 18-35 years of age, illiterate and living in rural areas. Marivan had the highest maternal mortality compared to other surveyed cities (29.1%). Prenatal care (OR= 22.7), parturition agent (OR= 9.85), use of one of the method of family planning (OR= 2.5) and parturition method (OR= 2.3) had meaningful relationship with maternal mortality. Conclusion: According to findings of this research, it is possible to decrease the maternal mortality by improving prenatal care and family planning and preventing parturition by uneducated midwives and avoiding unnecessary cesarian sections.